Current status of bulk fill composites - Lamas Lara, César Augusto (2023)
The evolution of direct restorative materials for posterior dental pieces has led to the generation of simpler processes that are easier for the clinician to perform. This is how bulk fill composite resins arise, in order to simplify the technique and provide the clinician with speed and practicality when performing the restoration. Although it is true that these materials have been used, there is still a lot of ignorance on the side of the professional about how to use them correctly. In addition to certain limitations in published research since they are relatively new materials on the market. This research aims to review the literature in indexed databases to date on bulk fill resins, detailing clinical trials, composition and classification.